MANAJEMEN PEMBINAAN PRESTASI CABANG OLAHRAGA BULUTANGKIS DI KLUB PB. SURYA BAJA TULUNGAGUNG - BUDI PRASETYO, BAGUS Budi (Jurnal Prestasi Olahraga, 2013)
The number of badminton clubs that stand in the  Surabaya, of course trigger for people to set up a badminton club in other area as well as in local badminton club namely PB. Surya Baja Tulungagung. Achievement coaching in the sport of badminton is also influenced by many factors: factors trainers, facilities and equipment training, evaluation results of the matches, the ability of athletes and etc. In addition, the implementation of good management factors also affects the athletes, even though it is not a direct factor which one of them is in the form of financial management, arrangement and performance.This study aims to determine and assess the management of the sport of badminton coaching achievements applied in the PB Tulungagung Surya Baja club, as well as analyzing the studies of experts in the field of sport management. This research method was used a passive participation. The instrument was used a tape recorder, records and supporting documents such as a camera. The data collected through interviews, documentation and observation. The data analysis technique was used descriptive.The results obtained by interviews of administrators, coaches, athletes, parents, and community. PB Tulungagung Surya Baja club was established on August 1, 2004. Always join the official championship in Java and have won several categories at Surya Naga Cup championship in Malang, Mayor Cip in Kediri, Tulungagung Regent Cup and Cup KONI in Surabaya financing by fees without any sponsor. Training program conducted by the group as much as 3-4 times per week, held a try out or attend events / championships in East Java. The board of PB Surya Baja badminton club Tulungagung has been established and worked according to with their respective duties. The factors that determines the success of badminton athletes club in PB Surya Baja Tulungagung is the motivation and discipline of the athletes, the competent coaches support and direct responsibility to the athletes, the availability of good training building, the athlete school schedule and athlete?s parents support. Regular exercise has been carried out every week, sparring matches/friendly, more intensive training by the time of the match in East Java. The composition of the board was formed. Facilities and infrastructure is good enough. The management of financial resources was independently done by picking up fee each month of athlete in PB Surya Baja Tulungagung club. Key words: Management, Achievements